Public Knowledge of Simple Earthquake-Resistant Houses after the 2022 Pasaman Earthquake - Rezi Aulia Febriani; Taufika Ophiyandri; Benny Hidayat (CIVED, 2025)
The 2022 Pasaman earthquake caused significant infrastructure damage, including widespread housing losses. To mitigate future risks, constructing earthquake-resistant homes is crucial. While previous studies by Hariyanto in 2020 examined public awareness of such structures, they did not analyze behavioral changes after major disasters. This study addresses that gap by assessing how the earthquake influenced attitudes and construction practices in Nagari Kajai and Nagari Malampah. Using a quantitative approach, data were collected via a structured questionnaire, adapted from the 2021 BSPS Home Building Construction Guidebook. The survey covered five aspects: building materials, main structure, structural connections, construction quality, and post-earthquake behavioral changes. Accidental sampling was used, with 60 respondents from the two affected areas. Findings show that 60% of respondents have fair knowledge of earthquake-resistant housing, while 20% demonstrate good knowledge and 20% have poor knowledge. Pearson Correlation analysis indicates a weak but significant relationship between knowledge levels and gender (p = 0.002) and age (p = 0.034), while education and occupation showed no significant correlation (p = 0.168 and p = 0.141). Post-earthquake, a shift toward semi-permanent housing structures was observed, highlighting the need for standardized, affordable building regulations. Policymakers should collaborate with local builders to ensure effective knowledge transfer on earthquake-resistant construction. Future reconstruction efforts should integrate post-earthquake evaluations to assess long-term housing resilience.